Functions of cited sources in Indonesian research articles (RAs) in the History and Law disciplines - Warsidi Warsidi (Universitas Sanata Dharma, 2025)
Citation is very significant in academic writing because it may create engagements with earlier findings and improve academic reputations. Studies on this area within academic writings have been widely conducted with varied purposes, but citation functions have received a small portion of scholarly attention. Besides, studies on this area in the Indonesian context are hardly found in the literature. Understanding this need has encouraged me to analyze citation functions in Indonesian History and Law research articles (RAs) because these two disciplines have been rarely investigated in genre studies, particularly in the Indonesian context. To reach this purpose, this study analyzed 30 Indonesian RAs from the History and Law disciplines to discover whether the functions are either to provide background information, provide evidence, or present beliefs, ideas, and issues circulated. The results revealed that citations found in the present study function as background information, evidence, and to present beliefs, ideas, issues circulated. However, these functions appear differently in each section. While these findings theoretically may contribute to the literature regarding citation functions in each section, they practically may provide awareness of article authors regarding the functions of citations in writing RAs.